Beyond “Monologicality”? Exploring Conspiracist Worldviews - Franks, Bradley; Bangerter, Adrian; Bauer, Martin W.; Hall, Matthew; Noort, Mark C. (Frontiers in Psychology, 2017)
Conspiracy theories (CTs) are widespread ways by which people make sense of unsettling or disturbing cultural events. Belief in CTs is often connected to problematic consequences, such as decreased engagement with conventional political action or even political extremism, so understanding the psychological and social qualities of CTs belief is important. CTs have often been understood to be “monological”, displaying the tendency for belief in one conspiracy theory to be correlated with belief in (many) others. Explanations of monologicality invoke a nomothetical or “closed” mindset whereby mutually supporting beliefs based on mistrust of official explanations are used to interpret public events as conspiracies, independent of the facts about those events (which they may ignore or deny). But research on monologicality offers little discussion of the content of monological beliefs and reasoning from the standpoint of the CT believers. This is due in part to the “access problem” (Wood & Douglas, 2015): CT believers are averse to being researched because they often distrust researchers and what they appear to represent. We used several strategies to address the access problem, and investigated the symbolic resources underlying CTs by reconstructing a conspiracy worldview - a set of beliefs held by CT believers about important dimensions of ontology, epistemology, and human agency. To do this, we analysed media documents, conducted field observation, and engaged in semi-structured interviews,. We describe six main dimensions of a conspiracy worldview: Views of the nature of reality, the self, the outgroup, the ingroup, action, and the future. We also describe a typology of five types of CT believers, which vary according to their positions on each of these dimensions. Our findings converge with prior explorations of CT beliefs but also revealed novel aspects: A sense of community among CT believers, a highly differentiated representation of the outgroup, a personal journey of conversion, variegated kinds of political action, and optimistic belief in future change. These findings are at odds with the typical image of monological CT believers as paranoid, cynical, anomic and irrational. For many, the CT worldview may rather constitute the ideological underpinning of a nascent pre-figurative social movement.